(untitled) (Applied Biological Research, 2018)
Control of Botryotinia ricini (Godfrey) Whetzel., gray mold pathogen of castor, is a challenge due to the lack of known sources of complete resistance and effective disease management practices. Isolation of pure culture of causal pathogen and its profuse sporulation are imperative for any pathological or molecular understanding of infection or resistance mechanisms and host-pathogen interactions. Season-dependent disease occurrence coupled with sparse conidial production in vitro has been a serious constraint. A culture medium (BRS) based on V8 juice broth supplemented with salts and minerals was developed and culture method and conditions optimized for profuse in vitro sporulation of gray mold fungus. ITS barcoding identified the isolate from Hyderabad as Amphobotyrs ricini A. ricini isolate IRHT-S1) which was closely related to A. ricini strain Cop Ar5. Phylogenetic analysis of the isolate with 20 related fungal species revealed that A. ricini forms a separate clade. Studies on growth response, culture characteristics and sporulation of A. ricini in different media ingredients revealed that the culture morphology differed with medium composition, especially in medium with 60 g L-1 dextrose, while capsule/ epicarp extract was dispensable. The addition of salts such as MgSO4 (1.0 g L1), KCl (1.0 g L-1) and FeSO4.7H2O (0.02 g L-1) favoured sporulation.